METHODS OF DEVELOPING STUDENTS' CREATIVE ACTIVITY THROUGH ART WORKS IN PRIMARY EDUCATION (Academia Science Repository, 2023)
In this article, ideas are given to primary school students about ways to develop their creative activity through artistic works.